Structural stability of antimicrobial peptides rich in tryptophan, proline and arginine: a computational study. Issue 8 (24th May 2022) - Marimuthu, Sathish Kumar; Nagarajan, Krishnanand; Perumal, Sathish Kumar; Palanisamy, Selvamani; Subbiah, Latha
Abstract: The host defense peptides or antimicrobial peptides (AMPs) often contain short sequence of amino acids, either positive or negatively charged and express broad-spectrum antibacterial, antiviral and antifungal activity. Many researchers had reported that tryptophan, arginine and proline rich AMPs have a promising source of next-generation antibiotics. Nowadays, AMPs are used as a possible therapeutic source for future antibiotics. In the present study, the amino acid sequences of 2924 AMPs belonging to various sources rich in Tryptophan, Proline and Arginine was chosen for investigation. The AMPs were further categorized according to their source, structure and antimicrobial activities. The AMPs with tryptophan, arginine, proline residues in abundance with maximum sequence length of 20 amino acids alone was obtained. Homology modeling was performed with PEP-FOLD and the modeled structures were evaluated using RAMPAGE to identify the structural information. Further, the stability of peptide in aqueous condition was probed using molecular dynamics simulations. Communicated by Ramaswamy H. Sarma